PERLINDUNGAN HUKUM BAGI KORBAN KEKERASAN BERBASIS GENDER: PERLINDUNGAN HUKUM BAGI KORBAN KEKERASAN BERBASIS GENDER - admin, Admin; Wirda Ayu Putri; Ach. Syamsul Askandar; Rudi Cahyono (STIH Zainul Hasan Kraksaan Kraksaan, 2024)
Abstract Sexual violence is one of the most serious and far-reaching forms of gender-based sexual violence. Sexual violence can occur in various contexts, including during disasters. Disasters can create vulnerable conditions for women and girls to become victims of sexual violence. PPPA Ministerial Regulation No. 13 of 2020 provides comprehensive protection for victims of sexual violence in disasters. This protection includes prevention, treatment and recovery. This research aims to find out what forms of gender-based violence exist and how legal protection works in efforts to restore the condition of children who have experienced trauma due to sexual abuse. The method used in the research is Normative Juridical, namely by examining statutory regulations and researchers also use a conceptual approach so that in this writing it refers to the views of scholars and legal doctrines. The results of the research in preparing this thesis, the first form of gender-based violence, namely rape/attempted rape, sexual abuse, sexual exploitation, sexual violence, physical violence, psychological violence, economic neglect, sexual slavery, forced abortion, forced marriage, and trafficking of women for other purposes. sexual. Second, according to article 1 number 2, Law Number 35 of 2014 concerning Child Protection, it is stated that: Child protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate, optimally in accordance with their dignity. and human dignity and receive protection from violence and discrimination. Such as protection in the fields of religion, health, education, social and special protection. Keywords : legal protection, victim, gender based violence